Microbial quality of linseed and fibre hemp plants during growing and harvest seasons - Koivula, M.; Kymäläinen, Hanna-Riitta; Vanne, Liisa; Levo, Seija; Pehkonen, Aarne; Sjöberg, Anna-Maija (MTT Agrifood Research Finland, 2004)
Öljypellavaa ja kuituhamppua voidaan käyttää moniin teollisiin sovelluksiin. Tässä tutkimuksessa mitattiin pellavan ja kuituhampun korsien mikrobiologista laatua vuosien 2001 ja 2002 kasvukausien ja korjuun aikana. Mikrobiologisissa määrityksissä käytettiin Hygicult® TPC- ja Y&F -kastolevyjä ja pintaviljelymenetelmää. Kasvukauden 2001 aikana olosuhteet olivat pääasiassa kosteat, kun taas kasvukausi 2002 oli melko kuiva ja lämpimämpi kuin kasvukausi 2001. Homeiden ja bakteerien määrä kasveissa lisääntyi huomattavasti kasvukauden 2001 lopussa sekä hampussa että pellavassa. Myös kasvukauden 2002 lopussa home- ja bakteerimäärät lisääntyivät, mutta muutos oli tasaisempaa kuin vuoden 2001 kasvukauden aikana. Vuoden 2001 kasvukauden lopussa home- ja bakteeripitoisuudet olivat suurempia kuin 2002 kasvukauden lopussa. Kasveista tunnistettiin mm. seuraavia homesukuja: Cladosporium, Fusarium, Penicillium, Mucor ja Alternaria. Tulosten perusteella mikrobiologiseen turvallisuuteen on kiinnitettävä huomiota koko tuotantoketjussa viljelystä ja korjuukaudesta alkaen.

Linseed (Linum usitatissimum L.) and fi bre hemp (Cannabis sativa L.) can be used as raw materials in various applications. In this study, microbiological quality and meteorological measurements were made during the growing seasons and harvesting periods of 2001 and 2002. The microbiological analyses were carried out with Hygicult® TPC and Y&F dipslides, and with a surface spreading method using Plate Count and Potato Dextrose agars. During the growing season of 2001 the conditions were mostly humid, whereas the growing season of 2002 was rather dry and warmer than that of 2001. The lack of water during the growing season of 2002 affected the growth of the plants. In the case of both hemp and fl ax, the mould and bacterial contents (cfu gdw-1) increased markedly at the end of the growing season of 2001. During the growing season of 2002 the increase in mould and bacterial contents was noticeable but more constant throughout the whole growing season. At the end of the growing seasons, the mould and bacteria contents were higher in 2001 than in 2002. The genera of moulds identifi ed included Cladosporium, Fusarium, Penicillium, Mucor and Alternaria. The microbiological safety should be controlled during the whole production chain, beginning with the cultivation and harvesting periods.
Keywords: Ka; pellavat; Linum usitatissimum; hamppu; Cannabis sativa; laatu; Linum usitatissimum L.; Cannabis sativa L.; Microbial quality; Growing season